An Empirical Investigation and Detailed Critical Analysis of Administration and Management of GOI Under the Leadership of Narendra Modi between 2014 To 2021 - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
Under Narendra Modi's able leadership, India has bagged some outstanding achievements and perhaps some of the biggest ones. Amongst all, one initiative of the Modi government that is being appreciated the most is making India free from open defecation. The net aim is to ensure the total sewage treatment takes this considerable initiative forward. Rivers are considered to be holy in the Indian culture. It is essential to ensure that this aim is executed and monitored enthusiastically and with utmost professionalism. India has also surpassed countries like France for becoming the sixth-largest economy globally and is still behind China, the USA, the UK, Japan, and Germany. In the past few months, the GOI has been maintaining its stance that it would be under the three top economies of the world by the year 2030. However, India has already become the third-largest economy globally regarding purchase power parity scale, only behind the USA and China. The Narendra Modi government is often criticized by its opposition for making many foreign trips. However, we cannot ignore that Narendra Modi's trips to different nations have helped our country make many friends. Whether it is about a warm relationship with Obama, Trump, or attending the Ganga Aarti with Prime Minister of Japan, Shinzo Abe, Narendra Modi has developed relationships that benefit our country in the long run.